Using RStudio to Engage School Students in Data Science - Alhammouri, Ahmad M; Al-Ouran, Rami (Ohio Journal of School Mathematics, 2021)
In this article, we provide an activity on how to engage high school students in data science projects. We discuss the data science framework before we present and solve a data science activity using the RStudio development environment. The code and data used in the activity are provided through easy-to-use downloadable online links.